Empowering learners’ reflective thinking through collaborative reflective learning - Yaacob, Aizan; Mohd Asraf, Ratnawati; Raja Hussain, Raja Maznah; Ismail, Siti Noor (Gate Association for Teaching and Education, 2021)
This paper is based on an action research that aimed to explore students’ reflective thinking through reflective collaborative learning. Drawing on multiple methods collected through focus group interviews, reflections, and online feedback, this paper examines the processes in which students develop their collaborative reflective learning to provide peer feedback to improve each other’s reflective writing. Two moments of intervention were set during the project to improve students’ critical questioning and reflective writing. Overall, reflective thinking via collaborative reflective learning promotes knowledge sharing, enhances pedagogical methods and theory, increases understanding of learner characteristics, and fosters professional self-development.